Insulin Treatment Is Associated With Improved Fetal Placental Vascular Circulation in Obese and Non-obese Women With Gestational Diabetes Mellitus - Barda, Giulia; Bar, Jacob; Mashavi, Margarita; Schreiber, Letizia; Shargorodsky, Marina (Frontiers in Endocrinology, 2019)
Objective: The present study was designed to investigate the impact of carbohydrate restriction and insulin treatment on placental maternal and fetal vascular circulation in obese and non-obese women with gestational diabetes mellitus (GDM). Design and methods: 192 women with GDM who gave birth and underwent a placental histopathological examination at Wolfson Medical Center, Israel, were included in the study: 123 women who were treated with carbohydrate/calorie restriction diet (Group 1) and 69 women who were treated with diet plus insulin (Group 2). Additionally, each group was divided into two subgroups according to pre-pregnancy BMI: non-obese and obese. Results: Maternal vascular malperfusion lesions did not differ significantly between groups. Vascular lesions related to fetal malperfusion were significantly lower in GDM women treated by insulin and diet compared to women with diet alone (p=0.027). Among fetal malperfusion lesions, villous changes consistent with fetal thrombo-occlusive disease (FTOD) were significantly lower in women treated with diet plus insulin and lowest in GDM women with prepregnancy BMI <30 (0%, 3.5%, 13% and 26.5% respectively, p=0.009). In the logistic regression analysis, insulin treatment was significantly associated with a decreased rate of villous changes consistent with FTOD (OR 0.97, 95% CI 0.12-0.80, p=0.03). Prevalence of gestational hypertension was higher in obese women of both treatment groups (p=0.024). Conclusion: Combination of obesity and GDM increased rate of FTOD and prevalence of gestational hypertension. Carbohydrate restriction diet plus insulin treatment was associated with improved fetal placental vascular circulation, especially in GDM women with prepregnancy BMI <30.